2011
DOI: 10.1007/s10815-011-9630-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cumulus cells removal after 6 h co-incubation of gametes on the outcomes of human IVF

Abstract: The present results indicate that cumulus cells removal at 6 h of insemination is a relatively safe operation, which yielded comparable normal fertilization rate, multinucleation and clinical pregnancy rates compared with 20 h group. This protocol may be beneficial for early obsevation of fertilization failure and make early rescue ICSI possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
62
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 28 publications
4
62
1
Order By: Relevance
“…This result supports the previous data [1,21] but is inconsistent with another report by Wei et al [19], which have shown a decrease in the quantity of available embryo rate. The different study designs could explain these conflicting results.…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations
“…This result supports the previous data [1,21] but is inconsistent with another report by Wei et al [19], which have shown a decrease in the quantity of available embryo rate. The different study designs could explain these conflicting results.…”
Section: Discussioncontrasting
confidence: 81%
“…In a study by Chen and Kattera [1], tripronuclear Patients with fertilization failure were not included rate was 6.1 % was obtained. 7.5 % polyspermy rate was observed by Xiong et al [21]. It should be noted that the cumulus cells were removed at 6 h of insemination in the latter two studies.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…If fertilisation failure is caused when binding of the spermatozoon to the zona pellucida, rescue ICSI may work; however, if the spermatozoon can penetrate the ovum successfully, but encounter difficulties in the subsequent oocyte activation and pronucleus formation, rescue ICSI will be ineffective. To determine the need for rescue ICSI based on the extrusion of 2PB 4-6 h after insemination has become a widely recognised approach (Chen & Kattera, 2003;Xiong et al, 2011;Zhu et al, 2011a,b). At 4-6 h after fertilisation, the extrusion rate of 2PB ranges from 78 to 86% ( Van den Bergh et al, 1995;Suppinyopong et al, 2000;Jin et al, 2014).…”
Section: Discussionmentioning
confidence: 99%